Military Occupational Specialty Codes: Utility in Predicting Inhalation Exposures in Post-9/11 Deployers. Issue 12 (December 2019) - Zell-Baran, Lauren M.; Meehan, Richard; Wolff, Jenna; Strand, Matthew; Krefft, Silpa D.; Gottschall, E.B.; Macedonia, Tony V.; Gross, Jane E.; Sanders, Oscar L.; Pepper, Gabriel C.; Rose, Cecile S.
Abstract : Objective: The aim of this study was to examine military occupational specialty (MOS) codes to identify those at risk from inhalation exposures during Southwest Asia deployment. Methods: Exposure intensity to diesel exhaust, sandstorms, burn pit smoke, combat dust, and occupational vapors/dusts/gases/fumes (VDGF) were scored for all Army/Marine MOS codes by an expert panel. Based on MOS code, panel-rated exposure scores were compared with questionnaire data from military personnel with postdeployment respiratory illnesses. Results: All exposures except VDGF were rated higher (range P < 0.0001 to P = 0.003) for combat versus noncombat MOS codes. Deployers with respiratory illnesses reported more intense exposure to diesel exhaust ( P < 0.0001), burn pit smoke ( P < 0.0001), and sandstorms ( P = 0.005) compared with panel raters. These deployers clustered in MOS codes rated highest for inhalation hazard exposure intensity. Conclusions: MOS codes are useful in identifying high-risk military occupations where medical surveillance and exposure control should be focused.